Waste management costs reduction and the recycling profit estimation from the segregation programme in Malaysia - Rangga, Josfirin Uding; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza; Karuppiah, Karmegam (Universiti Putra Malaysia Press, 2022)
This study aimed to estimate the potential waste management cost reduction and the recycling profit from the segregation programme implemented in Malaysia. The assessment was done among the states that implemented a waste segregation programme in Malaysia, a Southeast Asia country with a GDP of 364.7 billion USD. The solid waste (tonnes) data were collected from the Solid Waste Management and Public Cleansing Corporation, Malaysia, and analysed using mathematical models. On average, 2.69 million tonnes per year (t/yr) of waste were disposed of in the landfills, and 1,680 t/yr of waste was segregated, equivalent to 0.06%. Plastic (30.49%–39.48%) and paper (31.35%–40.88%) were the major components of segregated waste. Implementing the waste segregation program avoids the cost of waste disposal in landfills, potentially at 61,000 USD/yr and generating 130,000 USD/yr recycling profits. Therefore, the government should strengthen the programme to increase the segregation rate and provide a significant income to the community.